Use of electrochemical energy storage systems in autonomous power supply systems to reduce fuel consumption of power installations - A. I. Fedotov; E. A. Fedotov; A. F. Abdullazyanov (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. In remote areas in the absence of centralized power supply, energy conservation is one of the key factors for the successful development of the region. The use of electrochemical energy storage systems contributes to the saving of liquid or gaseous fuel of power plants used in autonomous power supply systems. Domestic manufacturers have created modular-type mobile energy storage systems designed for their rapid deployment in almost any territory and operating in the range from several hundred kilowatts in a single design to complexes of tens of megawatts. METHOD. The method of indefinite Lagrange multipliers was used in application to the power profiles of the load of a discrete form to select the parameters of the electrochemical energy storage, causing the minimization of fuel consumption. The obtained mathematical model uses the power profiles of the load, formed by its duration, and is focused on the simplest algorithm for the numerical search for the extremum of a function by changing its argument, without solving the optimization nonlinear equation. The method includes the choice of the duration of the discharge of the energy storage. RESULTS. The influence of the energy storage device on the reduction of fuel consumption is shown. The technique is valid for convex consumption characteristics of power plants. In the context of predicted changes in power profiles (work / weekend days), optimal control scenarios are calculated individually. CONCLUSION. The use of the proposed mathematical model provides quick calculations of the economic assessment of the use of electrochemical energy storage. For gas piston power plants, where they are required to stabilize the parameters of power quality, their commercial attractiveness is significantly higher than for power plants of another type.